2021
DOI: 10.2196/25138
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and Wearable Technology for the Monitoring of Diabetes-Related Parameters: Systematic Review

Abstract: Background Diabetes mellitus is a metabolic disorder that affects hundreds of millions of people worldwide and causes several million deaths every year. Such a dramatic scenario puts some pressure on administrations, care services, and the scientific community to seek novel solutions that may help control and deal effectively with this condition and its consequences. Objective This study aims to review the literature on the use of modern mobile and wear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…In this way, it would be possible to follow patients remotely, especially in cases of chronic and disabling diseases, avoiding the worsening of psycho-physical conditions and the onset of a sense of abandonment, as recent studies on the effects of the pandemic have shown. Several systems are now available for the remote monitoring of subjects with specific pathologies in the real world, including diabetes [ 91 ], osteoarthritis [ 92 ], respiratory dysfunctions [ 93 ], amyotrophic lateral sclerosis [ 94 ], and cognitive rehabilitation [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, it would be possible to follow patients remotely, especially in cases of chronic and disabling diseases, avoiding the worsening of psycho-physical conditions and the onset of a sense of abandonment, as recent studies on the effects of the pandemic have shown. Several systems are now available for the remote monitoring of subjects with specific pathologies in the real world, including diabetes [ 91 ], osteoarthritis [ 92 ], respiratory dysfunctions [ 93 ], amyotrophic lateral sclerosis [ 94 ], and cognitive rehabilitation [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mobile and wearable technology for the monitoring of diabetes-related parameters: Systematic review [19] 2021 -Focused on the devices rather than machine learning Mobile apps for the treatment of diabetes patients: a systematic review [20] 2021 -Presents only the management of diabetes using mobile applications.…”
Section: Title Year Limitationsmentioning
confidence: 99%
“…In summary, the management of blood glucose levels using AI and wearable devices is a safe and effective method, which can effectively reduce the occurrence of diabetic complications such as retinopathy as well as diabetic foot problems [25,26,44] . Information integration systems based on AI and blockchain technology can make a risk assessment and timely warning for diabetic ketoacidosis, hypoglycemia, and hyperglycemic hyperosmolar syndrome, which will greatly enhance the safety of patients with diabetes mellitus [42,45] .…”
Section: Diabetes Mellitusmentioning
confidence: 99%